1990
DOI: 10.3168/jds.s0022-0302(90)78980-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feeding Aspergillus oryzae Fermentation Extract or Aspergillus oryzae plus Yeast Culture plus Mineral and Vitamin Supplement on Performance of Holstein Cows During a Complete Lactation

Abstract: The addition of Aspergillus oryzae fermentation extract (Amaferm) increased milk flow and mean 3.5% FCM production during the latter stages of the full lactation trial compared with the control group and the Aspergillus oryzae fermentation extract plus yeast culture plus mineral-vitamin supplement (VitaFerm) group. Based on the differences observed when FCM production was determined for the cows at various stages of lactation, Amaferm apparently had its greatest effect during the early stages of the lactation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 3 publications
1
16
0
Order By: Relevance
“…On the other hand, Higginbotham et al (2004) reported that feeding 5 g/day of AO to early lactation Holstein cows had no effect on lactation performance and rumen parameters. In the current studies, including AO slightly increased milk fat content and this agrees with other trials (Kellems et al 1990; Robinson and Garrett 1999;Dann et al 2000;Lehloenya et al 2008;Ramsing et al 2009).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, Higginbotham et al (2004) reported that feeding 5 g/day of AO to early lactation Holstein cows had no effect on lactation performance and rumen parameters. In the current studies, including AO slightly increased milk fat content and this agrees with other trials (Kellems et al 1990; Robinson and Garrett 1999;Dann et al 2000;Lehloenya et al 2008;Ramsing et al 2009).…”
Section: Discussionsupporting
confidence: 93%
“…Perhaps the dynamics of ruminal digestion differed between the two diets, which might have affected performance responses to AO as has been previously speculated (Williams et al 1991 fungi supplements resulted in 5% higher milk yields. In addition, other papers have also reported increased milk production in cows fed diets with fungal products (Kellems et al 1990;Robinson and Garrett 1999;Dann et al 2000;Lehloenya et al 2008;Ramsing et al 2009). On the other hand, Higginbotham et al (2004) reported that feeding 5 g/day of AO to early lactation Holstein cows had no effect on lactation performance and rumen parameters.…”
Section: Discussionmentioning
confidence: 94%
“…1993. 71:1032-1040(Kellems et al, 1990) on production of fat-corrected milk. Response to A 0 has been greatest in earlylactation cows and in cows fed high-concentrate rations (Gomez-Alarcon et al, 1991), which are typically high in NFC.…”
Section: Supplementation Of Diets Of Lactating Cows Withmentioning
confidence: 99%
“…Milk yield increased by 6.03% in prilled fat supplemented cows (Rajesh et al, 2014), while Increase in milk yield due to yeast culture feeding usually range between 1 and 2 kg/d (Robinson et al, 1999). Microbial additives such as yeast cultures had the greatest positive effect on cows in early lactation, increasing milk yield over that of control cows (Kellems et al, 1990). S. cerevisiae supplementation increased organic matter digestibility thus allowing higher energy availability for milk yield and reduced fat mobilization in buffalo (Campanile et al, 2008).…”
Section: Fatty Acid Profilementioning
confidence: 99%